TEACHER STRATEGY IN REDUCING HYPERACTIVE BEHAVIOR OF CHILDREN WITH SPECIAL NEEDS DURING PANDEMIC COVID-19 AT SLBN SUKOHARJO - Nurhidayat Nurhidayat; Gatot Jariono; Eko Sudarmanto; Ardhian Tomy Kurniawan; Chandra Triadi; Maimunah Nur Anisa (Yayasan Education and Social Center, 2021)
The purpose of the teacher's role in reducing the hyperactive behavior of children with special needs. The population and sample in this study were teachers and parents at the SLBN Sukoharjo, Central Java Province totaling 40 people, carried out on February 20, 2021. Data collection techniques were obtained by observation, distributing questionnaires, and interviews. This research is a type of descriptive research using quantitative and qualitative approaches. The data analysis in this study used a descriptive analysis of presentations using Microsoft word 2019. The results showed that in reducing the hyperactive behavior of children with special needs, an active role was carried out between teachers and parents in synergy in the distance learning process during the covid_19 pandemic. In this study, further research is needed to reduce the hyperactive behavior of children with special needs. In this study, it can be concluded that the teacher's strategy in reducing the hyperactive behavior of children with special needs during the covid_19 pandemic is through the teacher's role as a motivator, companion, learning designer, learning artist, mediator, motivator, and innovator